Occupational Exposure to Hexavalent Chromium, Nickel and PAHs: A Mixtures Risk Assessment Approach Based on Literature Exposure Data from European Countries - Tavares, Ana Maria (2022)
This article belongs to the Special Issue Human Biomonitoring in Health Risk Assessment: Current Practices and Recommendations for the Future.